Lessons learned and future challenges - Henning, Christian; Badiane, Ousmane (Springer, 2018)
The contributions of this book can be understood as a continuation of the ongoing evidenced-based debate on the role of agriculture and participatory policy processes in reducing poverty. In this context, the economic modelling approaches presented in this book provide new insights into the agricultural versus nonagricultural growth nexus. Besides growth-poverty linkages, these particularly include nutrition-growth-poverty linkages and policy-growth linkages to identify key sectors and key policies within an effective Pro-Poor-Growth-strategy. In contrast to existing approaches, the political process has been explicitly integrated into this quantitative analyses. Thus, the derived CGPE approach allows a more comprehensive growth-poverty analysis, including not only the impact of biased political incentives, but also the lack of adequate political knowledge and ownership, respectively, as a source of low political performance. Political knowledge is reflected by policy beliefs which in turn are formed by political agents through communication and observational learning processes organized in policy networks. Effective participatory policy processes are characterized by policy network structures implying stakeholder influence that reflects both, the size of the society groups represented and the specific political knowledge of the stakeholder organizations. Apart from stakeholders, voters also play an important role in determining effective participatory policy processes. Voter behavior, i.e. the importance of policy versus non-policy voting motives, significantly determines both, governmental incentives and lobbying influence. While non-policy voting implies policy failure due to government capture and low government accountability, policy voting limits government performance depending on the extent to which voters’ policy beliefs are biased. Future challenges correspond to three areas: (1) modelling complex policy-growth linkages via policy impact functions (2) designing effective communication between science and political practice that allow an effective policy learning and (3) modelling voter behavior, especially the formation of voter beliefs in a political mass communication processes.